Effects of torque direction, shape, size, sensation and technique on pinch force - Ng, Poh Kiat (2015)
In manual work, high pinch force exertions can be associated with the development of hand-related musculoskeletal disorders. Conversely, low pinch force exertions can cause slippages, which can lead to hand-related injuries. In association to this, researchers found that handgrip force is significantly affected by torque direction, size and sensation. However, there appear to be few related studies on the effects of different pinch parameters on pinch force. The novelty of this research lies in its aim which is to disclose the effects of pinch parameters such as the torque direction of pinches, shape and size of objects, sensation of fingers and technique of pinches on pinch force. The research uses a full factorial design of experiment with 5 variables. Three common types of screw knobs of 3 different shapes (spherical, cylindrical, 5-lobes) and sizes (large, medium, small) are identified and fabricated for the experiment, which involves approximately 30 participants. Participants are required to pinch the knobs with 3 commonly-used pinch techniques (lateral, 3-jaw chuck, pulp-2) while wearing pressure sensors that record the forces between the fingertips and knobs. The forces are recorded in Minitab 16. The analysis of variance is used to determine the effects of the main and combinatorial factors on pinch force while the response surface regression and response optimisation are used to determine the optimised pinch force response. It is found that pinch force is significantly affected by all the main parameters. For the two-way interactions, only interactions of sensation with pinch technique, sensation with size, pinch technique with torque direction, pinch technique with size, torque direction with size and shape with size are significant. A response surface regression model representing these effects is also generated. This is useful for the pinch force prediction using any of the parameter combinations. By defining the predicted maximum, minimum and average pinch force responses through the response optimisation, a total of 3 major factorial combinations were identified. The findings potentially aid the development of both safety and design guidelines for ergonomic precision designs. Although much research is required, it is hoped that this study can serve as a precursory guideline for researchers to further expound ideas related to pinch force capacity.